(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose - The purpose of this study is to determine how blended learning, teleworking challenges, knowledge, strategic responses in crisis situations, perceived seriousness, peoples’ adherence to Covid-19 preventative measures, social stigma, age and gender relate to the outcome variable “Psychological Distress during the Covid-19 pandemic” in Qatar. Design/methodology/approach - The data analyzed in this study was originated from a nationally online (web) survey of residents in Qatar during the Corona crisis in 2020. The number of questionnaires with complete data on valid items for multivariate analysis is 1683. By using factor analysis as a data reduction technique and to establish the construct validity of the questionnaire, Kaisers-Meyer-Olkin (KMO) and the Bartless test of sphericity showed that eight extracted dimensions are valid and can be used in the structural equation model (path analysis). Findings - In regressing the outcome variable “Psychological distress due to Covid-19 "on the seven extracted dimensions as well as on “Age” and “Gender”, it is found that the multiple coefficient of determination is highly significant. “Psychological distress due to Covid-19” is determined by all explanatory significant variables. Moreover, the study findings suggest that the explanatory variables indentified in the causal model generate both positive and negative direct effects. What’s more, the outcome variable “Psychological Distress due to Covid-19” is a complex observable phenomenon calling for multiple interventions. Apart from individual significant direct positive or negative effects, all indirect effects with the exception of knowledge increase the total (as the sum of direct and indirect) effects. Findings of this study provide strategic insights and useful thinking that have significant implications for understanding “Psychological distress due to Covid-19.” Original value - To the best of the researchers’ knowledge, this is the first path analytical investigation of “Psychological distress due to Covid-19” in Qatar. This novel context should provide a useful base for further studies as well as for policy making.